Ti–15Zr and Ti–15Zr–5Mo Biomaterials Alloys: An Analysis of Corrosion and Tribocorrosion Behavior in Phosphate-Buffered Saline Solution - Santos, Adriana Alencar [UNESP]; Teixeira, Jean Valdir Uchôa [UNESP]; Pintão, Carlos Alberto Fonzar [UNESP]; Correa, Diego Rafael Nespeque [UNESP]; Grandini, Carlos Roberto [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP] (MDPI, 2023)
It is crucial for clinical needs to develop novel titanium alloys feasible for long-term use as orthopedic and dental prostheses to prevent adverse implications and further expensive procedures. The primary purpose of this research was to investigate the corrosion and tribocorrosion behavior in the phosphate buffered saline (PBS) of two recently developed titanium alloys, Ti–15Zr and Ti–15Zr–5Mo (wt.%) and compare them with the commercially pure titanium grade 4 (CP–Ti G4). Density, XRF, XRD, OM, SEM, and Vickers microhardness analyses were conducted to give details about the phase composition and the mechanical properties. Additionally, electrochemical impedance spectroscopy was used to supplement the corrosion studies, while confocal microscopy and SEM imaging of the wear track were used to evaluate the tribocorrosion mechanisms. As a result, the Ti–15Zr (α + α′ phase) and Ti–15Zr–5Mo (α″ + β phase) samples exhibited advantageous properties compared to CP–Ti G4 in the electrochemical and tribocorrosion tests. Moreover, a better recovery capacity of the passive oxide layer was observed in the studied alloys. These results open new horizons for biomedical applications of Ti–Zr–Mo alloys, such as dental and orthopedical prostheses.
Keywords: biomaterial titanium alloys; corrosion; EIS; tribocorrosion